Improving Students’ Career Decision Making through ODI —A Course Design of Career Exploration in the International College of Zhejiang Yuexiu University of Foreign Languages - Chen, Chudan; Vinitwatanakhun, Watana (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
The research aims to improve students’ career decision making in terms of career decision making self-efficacy (CDMSE) through organization development interventions (ODI) based career exploration course. The course content was developed based on the cognitive information processing model, and a five-stage CASVE cycle (communication, analysis, synthesis, valuing, and execution) ODI was applied to assist with students’ career decision making. An application of organization development tools—Appreciative Inquiry, team building, goal setting, and plan making—was utilized together with self-assessments, occupation interviews and periodical reflection reports. A comparison between an experiment group (N=64) and a control group (N=64) was investigated, and mixed research methods of qualitative and quantitative data collection were employed to compare two groups’ pre-ODI and post-ODI performance in light of career exploration and career decision making self-efficacy, which were measured by Career Exploration Scale and Career Decision Making Self Efficacy Scale respectively. The research findings revealed that students who took the career exploration course had statistically significant gains in career exploration and career decision making self-efficacy, whereas no significant improvement was observed in the control group. The results can be concluded that ODI-based career exploration course is effective in improving students’ career decision making self-efficacy.